Description the female sex of Allicyrtaspis conicicersus Shi, Bian & Chang, 2013 (Orthoptera: Tettigoniidae: Meconematinae) - Cui, Zhenczhen; Wang, Huaizheng; Bian, Xun (Zootaxa, 2024)
This paper describes the female sex of Allicyrtaspis conicicersus Shi, Bian & Chang, 2013 based on the specimens deposited in Guangxi Normal University. The morphological illustrations of both sexes for A. conicicersus were provided.